Impact of biomass burning on soil microorganisms and plant metabolites: A view from molecular distributions of atmospheric hydroxy fatty acids over Mount Tai. Issue 10 (26th October 2016) - Tyagi, Poonam; Kawamura, Kimitaka; Fu, Pingqing; Bikkina, Srinivas; Kanaya, Yugo; Wang, Zifa
Abstract: Biomass burning events (BBEs) in the North China Plain is one of the principal sources of airborne pollutants in China and also for the neighboring countries. To examine the impact of BBEs on soil bacteria and other higher plant metabolites, their tracer compounds, hydroxy fatty acids (FAs), were measured in the bulk particulate matter (total suspended particles (TSP)) over Mount Tai during the period of wheat residue burning in June 2006. Higher inputs of epicuticular waxes and soil microorganisms during high BBEs (H; 6–14 and 27 June) relative to low BBEs (L; 15–26 and 28 June) were characterized by increased concentrations of homologous series of α ‐(C9 –C32 ), β ‐(C9 –C32 ), and ω ‐(C12 –C28 ) hydroxy FAs in TSP samples. However, their relative abundances were not significantly different between H‐BBEs and L‐BBEs, suggesting their common source/transport pathways. We also found higher concentrations of trehalose and mannitol (tracers of soil microbes), and levoglucosan (tracer of biomass combustion) during H‐BBEs than L‐BBEs. These results are consistent with hydroxy FAs, suggesting that they are associated with biomass combustion processes of agricultural wastes as well as re‐suspension of mineral dust and plant pathogens. In addition, enhanced concentrations of endotoxin and mass loading of Gram‐negative bacteria during H‐BBEs (117 endotoxin units (EU) m −3 and 390 ng m −3, respectively) were noteworthy as compared to those in L‐BBEs (22.5 EU m −3 and 75 ng m −3, respectively). Back trajectory analysis and fire spots together with temporal variations of hydroxy FAs revealed an impact of biomass burning on emissions and atmospheric transport of bacteria and plant metabolites. Key Points: Impacts of biomass‐burning emissions on soil microbes and plant metabolites Hydroxy fatty acids (FAs) in summertime aerosols collected over Mount Tai beta‐Hydroxy FAs as tracers to assess endotoxin and Gram‐negative bacteria in aerosols